The Work of the Sixth Committee of the United Nations General Assembly 2012-2013 - Pronto, Arnold (South African Yearbook of International Law, 2013)
The following is a review of the activities of the Sixth Committee of the General Assembly of the United Nations at the sixty-seventh and sixty-eighth sessions of the Assembly, held in 2012 and 2013 respectively. As described previously, the work of the Committee can be organised broadly into three types of activity: the substantive consideration of certain legal issues; the review of the annual work of expert legal bodies; and the discharge of certain oversight functions. A fourth function may be added: the review of requests for observer status in the General Assembly. During the period under review, the Committee dealt with a broad range of legal issues of international concern. As with any overview, depth of analysis is sacrificed on the altar of breadth of coverage.